Activity profiling of Serbian and some other European Merlot wines in inflammation and oxidation processes. (July 2019) - Majkić, Tatjana M.; Torović, Ljilja D.; Lesjak, Marija M.; Četojević-Simin, Dragana D.; Beara, Ivana N.
Abstract: Merlot are worldwide recognized red wines. Several studies show that red wines have health benefits, mainly due to their phenolic constituents. This study evaluates twelve Serbian and other five European (French, Italian, Macedonian, Slovenian, Spanish) Merlot wines in respect of their phenolic composition and biological activity. The latter was evaluated through a set of in vitro experiments related to common benefits of moderate red wine consumption in the prevention of cardiovascular diseases. Among the examined phenolics, the most abundant acid in all samples was the gallic acid (14.3–58.3 mg/L), catechin (9.1–49.3 mg/L) was the dominant flavonoid, malvidin-3- O -glucoside (2.63–66.5 mg/L) leading anthocyanin, whereas resveratrol was found in a usual concentration (0.18–4.67 mg/L). Differences determined in phenolic profiles, mainly in content of quercetin, rutin and p -coumaric acid, leaded to separation of Serbian from foreing Merlot wines. Results of standard antioxidant assays (DPPH, ABTS + and NO scavenger capacity reducing power (FRAP), lipid peroxidation) revealed French Merlot as the most potent, but also pointed out some Serbian samples. The correlation between the content of dominant phenolics and antioxidant activity was sporadic, but samples with the highest overall phenolic content, generally had higher antioxidant potential. Concentration of wines and number of cells in ant-inflammatory assay were chosen to mimic in vivo conditions. So, the potency of examined wines to decrease the production of macrophage-derived PGE2 and TXA2 (up to 65.5 and 47.9%, respectively), could be considered as in vitro evidence of positve health effect. Regarding the phenolic content and anti-inflammatory contribution of the most abundant compounds, no correlation was witnessed. In general, this study showed interesting potential of Serbian Merlot wines, comparable to health-promoting effects of renewed Eurepean ones. Graphical abstract: Unlabelled Image Highlights: The worldwide recognized Merlot red wine is regarded as foods with health benefits. Present phenolics reasonably contribute to distinction based on geographical region. Higher overall phenolic content was correlated with higher antioxidant potential. No correlation was found between phenolic profile and anti-inflammatory activity. In vitro effects on prevention of cardiovascular diseases were proven.